Kajian Pengelolaan Lubuk Larangan Sebagai Upaya Pelestarian Ikan di Desa Guguk Kecamatan Renah Pembarap Kabupaten Merangin - Andriyanto (BIOCOLONY, 2018)
The aims of this research was to study the conservation of aquatic resources based on local wisdom through the management of the Lubuk Larangan at Guguk Village, Merangin District, Jambi Province. The method that used in this study is a qualitative approach. Data collection was carried out through in-depth interviews with informants selected by purposive sampling of key informants there are Village Heads, Customary Figures, Religious Leaders, Community Leaders, and Lubuk Larangan Managers. The results showed that Guguk Village has a Lubuk Larangan that located in the Batang Merangin river named Lubuk Larangan Ujung Tanjung. The purpose of the Lubuk Larangan is as a means of conserving aquatic resources and for increasing village income. There are rules and sanctions for the community regarding the management of Lubuk larangan. Economically, the existence of lubuk guguk village was not satisfactory compared to other areas which are likely caused by illegal gold mining activities in the Batang Merangin River and other rivers which disrupt river ecosystems.